Environmental Intervention: An Activist Idea or Legal Tool? An Analysis of the Possibilities of Environmental Protection under the Principle of Non-Intervention - Berkant Akkuş (Annales de la Faculté de Droit d’Istanbul)
Climate change is arguably the single most important threat to all life on Earth. Through the 2015 Paris Agreement and annual United Nations (UN) climate change conferences, the international community has attempted to rally universal support for mandatory greenhouse gas emission reduction targets. If attained, it is likely that destructive global temperature rises would be at least slowed. The fact that States agree to pursue environmental protection objectives, but routinely fail to act accordingly provides essential context for this four-section critical discussion. ‘Environmental intervention’ as contemplated by this research topic is more than a mere activist idea. It necessarily represents a valid international law alternative given that the entire world faces a potentially catastrophic climate emergency. The various points considered in this discussion confirm that unilateral State intervention to prevent transborder pollution created in another State might seem justified under well-recognised ‘Responsibility to Protect’ principles. The materials assembled for present discussion purposes support an alternative conclusion. The combined effect of the international law emphasis placed on State sovereignty, and a dysfunctional, inconsistent international community commitment to achieving actual climate change mitigation likely condemns to failure any environmental intervention measures that the UN might advance through proposed treaties or similar international agreements.